Quality Control of Lime Juices from Iran - ANSARI, FARZANEH; REZAEI, KRAMATOLLAH (Asian Journal of Chemistry, 2010)
Lime samples from three major lime-producing locations of Iran were investigated for their quality control (total acidity, total soluble solid, total solid content, pH, ash content, alkalinity of ash and formol titration). Total soluble solid was significantly higher in limes from Jahrom than those from Roudan and Minab. Similarly, the average value of vitamin C content in limes obtained from Jahrom (37.9 ± 2.7 mg/ 100 mL,) was significantly higher than those of Roudan (34.2 ± 2.2) and Minab (35.3 ± 2.2). Other parameters also showed some differences. But, despite such differences, the ratios of total soluble solid to total acidity, so-called "maturity ratio," for the limes from the three regions were similar indicating that they had similar palatability levels.